GAYA PENCIPTAAN HADAWIYAH ENDAH UTAMI DALAM TARI BEDHAYA SANTRI - Utama, Ansilia Erna; Bantolo, Matheus Wasi (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
The research entitled “Hadawiyah Endah Utami’s Creation Style in Bedhaya Santri Dance” is an attempt to see the creation style of a choreographer in creating works. Bedhaya Santri Dance was created by Hadawiyah Endah Utami to fulfill Tatik Harpawati’s request who wanted an Islamic-themed dance for a wedding ceremony at Pendapa Ageng ISI Surakarta. This research aims to examine the creation style and expression in the dance. To uncover the problem, a qualitative method was used with a choreography approach supported by data collection through observation, interviews, and library studies. This study bases its analysis on Janet Adshead’s theory to understand the form and creation style in Bedhaya Santri dance, as well as the contribution of Adina Armelagos. The results of this study identify three main parts of the dance: forward movement, stopping movement, and backward movement. And there are several characteristics in this dance form that can be seen through its elements, including, all dancers are female, costumes use face curtains as a depiction of a woman's value, Islamic-themed music with verses from the book Al Barzanzi, floor patterns related to space and Javanese philosophy. This dance involves seven female dancers with music from Javanese gamelan and sholawat, providing a spiritual dimension. The costumes and makeup worn emphasize religious values, while Hadawiyah Endah Utami's creative style emphasizes calm and detailed Javanese techniques. This dance also depicts Islamic spirituality through flowing and intermittent movements, creating a distinctive style for choreographers to present innovation in Islamic dance.